2018
DOI: 10.1001/jamapsychiatry.2018.0039
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Estimating the Effect Sizes of Copy Number Variants on General Intelligence in Community-Based Samples

Abstract: Models trained on nonpathogenic deletions in the general population reliably estimate the effect size of pathogenic deletions and suggest omnigenic associations of haploinsufficiency with IQ. This represents a new framework to study variants too rare to perform individual association studies and can help estimate the cognitive effect of undocumented deletions in the neurodevelopmental clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
139
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 91 publications
(156 citation statements)
references
References 46 publications
9
139
1
1
Order By: Relevance
“…We previously reported that statistical models, trained on benign deletions in populations not selected for a clinical condition, can accurately estimate the effect-size of deleterious deletions on non-verbal IQ (NVIQ). (26) These results suggest that 1) the effect-size of deletions on NVIQ can be estimated using constraint scores, such as the "probability of being Loss-of-function Intolerant" (pLI, definition in textbox, Figure 1) (27), and 2) the effect of haploinsufficiency on NVIQ applies to a large proportion of the genome, consistent with a highly polygenic model. (28,29) Using pLI as an explanatory variable, we estimated that one third of the coding genes affect NVIQ by >1 point, when deleted.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…We previously reported that statistical models, trained on benign deletions in populations not selected for a clinical condition, can accurately estimate the effect-size of deleterious deletions on non-verbal IQ (NVIQ). (26) These results suggest that 1) the effect-size of deletions on NVIQ can be estimated using constraint scores, such as the "probability of being Loss-of-function Intolerant" (pLI, definition in textbox, Figure 1) (27), and 2) the effect of haploinsufficiency on NVIQ applies to a large proportion of the genome, consistent with a highly polygenic model. (28,29) Using pLI as an explanatory variable, we estimated that one third of the coding genes affect NVIQ by >1 point, when deleted.…”
Section: Introductionmentioning
confidence: 74%
“…As we previously observed in unselected populations (26), the variable selection procedure identified the sum of pLI scores as the variable that best explains the variance of NVIQ in the SSC for deletions (r 2 =0.013) and duplications (r 2 =0.004), compared to the Table S11 in the online supplement, Figure 2A).…”
Section: Effect-size Of Gene Dosage On General Intelligence In Probanmentioning
confidence: 96%
See 2 more Smart Citations
“…We have previously shown that linear models 19 using the sum of the "probability of being loss-of-function intolerant" (pLI) scores 20 of all genes included in a deletion can predict their effect-size on intelligence quotient (IQ) with a concordance of 75% with empirical measures.…”
Section: Introductionmentioning
confidence: 99%